Mechanical Thrombectomy for Acute Stroke Due to Large-Vessel Occlusion Presenting With Mild Symptoms - Liu, Feifeng; Shen, Hao; Chen, Chen; Bao, Huan; Zuo, Lian; Xu, Xiahong; Yang, Yumei; Cochrane, Alexia; Xiao, Yaping; Li, Gang (Frontiers in Neurology, 2021)
Purpose: To evaluate the safety and efficacy of mechanical thrombectomy (MT) for acute stroke due to large vessel occlusion (LVO), presenting with mild symptoms. Methods: A prospective cohort study of patients with mild ischemic stroke, and LVO was conducted. Patients were divided into two groups: MT group or best medical management (MM) group. Propensity score matching (PSM) was conducted to reduce the confouding bias between the groups. The primary outcome was functional independence at 90 days. The safety outcome was symptomatic intracranial hemorrhage (sICH). Univariate and multivariate logistic regression analyses were used to identify the independent factors associated with with outcomes. Results: Among the 105 included patients, 43 were in the MT group and 62 in the MM group. 43 pairs of patients were generated after PSM.There were no significant differences in sICH rates between two groups (p=1.000). The MT group had a higher proportion of independent outcomes (83.7% MT versus 67.4% MM; OR 2.483; 95% CI 0.886-6.959; P=0.079) and excellent outcomes (76.7% MT versus 51.2% MM; OR 3.150; 95% CI 1.247-7.954; P=0.013) compared to the MM group, especially in patients with stroke of the anterior circulation (P<0.05). Multivariate logistic regression analysis showed that small infarct core volume (P=0.015) and MT treatment (P=0.013) were independently associated with excellent outcomes. Conclusions: Our results suggest that MT in stroke patients, presenting with mild symptoms, due to acute LVO in the anterior circulation may be associated with satisfactory clinical outcomes. This trial is registered and publicly available on ClinicalTrials.gov. ( number NCT04526756).